15 Prevalence of ischaemic mitral regurgitation meeting coapt and mitra-fr criteria for mitraclip intervention – a cohort study of 1000 patients following myocardial infarction. (17th July 2020) - Sharma, Harish; Radhakrishnan, Ashwin; Brown, Samuel; May, John; Zia, Nawal; Joshi, Rashi; Ludman, Peter F; Townend, Jonathan; Doshi, Sagar N; Khan, Sohail Q; Zaphiriou, Alex; George, Sudhakar; et al.
Abstract : Background: Ischaemic mitral regurgitation (IMR) confers a poor prognosis. Transcatheter mitral edge-to-edge repair may improve outcomes but MITRA-FR and COAPT trials have produced conflicting results, attributed to different patient selection criteria. Following acute myocardial infarction (MI), the number of patients eligible for transcatheter mitral repair using MITRA-FR and COAPT eligibility criteria is not known, nor whether these criteria produce cohorts with significantly different characteristics. Purpose: To determine the number and characteristics of IMR patients qualifying for MITRA-FR and COAPT echocardiographic eligibility criteria amongst patients receiving coronary revascularization following acute MI. Methods: 1000 consecutive patients admitted to the Queen Elizabeth Hospital Birmingham with acute MI who underwent coronary angioplasty were included. Early inpatient TTE was performed by accredited echocardiographers using standard multiparametric quantification, including (where possible) proximal isovelocity surface area (PISA), effective regurgitant orfice area (EROA), vena contracta (VC) regurgitant volume (RVol), regurgitant fraction (RF) and left ventricular ejection fraction (LVEF). Patients within our admission population fulfilling the following echo criteria were identified: MITRA-FR: LVEF 15-40% and EROA > 0.2cm2 or RVol > 30ml COAPT: LVEF 20-50% and either: Tier 1: EROA > 0.3cm2 or pulmonary vein flow reversal Tier 2: EROA > 0.2cm2 and <0.3cm2 with one of the following: RVol > 45ml/beat; RF > 40%; VC > 0.5cm; Tier 3: EROA <0.2cm2 or not measured and > 2 of the following: RVol > 45ml/beat; RF > 40%; VC > 0.5cm; PISA > 0.9cm but continuous wave of MR jet not done; Large (> 6cm) holosystolic jet wrapping around left atrium; Peak E wave velocity > 150cm/s. Results: MR was observed in 294/1000 patients (29.4%) post-MI, graded as mild (76%), moderate (21%) and severe (3%). Based on MR characteristics alone (not including LVEF), the number of patients fulfilling MITRA-FR and COAPT eligibility criteria were 23 (7.8% of all IMR) and 24 (8.1% of all IMR) respectively. Both groups had a similar ratio of moderate:severe MR (74:26% vs 75:25%), EROA (0.34+/-0.13cm2 vs 0.35+/-0.13cm2), VC (0.6+/-0.2cm vs 0.6+/-0.2cm), RVol (52+/-24ml vs 51+/-25ml), indexed LA volume (LAVi) (54+/-20ml/m2 vs 51+/-20ml/m2), indexed LV end-diastolic volume (LVEDVi) (62+/-17ml/m2 vs 63+/-18ml/m2), LVEF (48+/-13% vs 47+/-13%) and mortality (MITRA-FR: 23% vs COAPT: 29%, p=0.9243). After including LVEF as a criterion, the number of patients eligible for MITRA-FR and COAPT were just 5 (1.7% of all IMR) and 14 (4.7% of all IMR) respectively. As expected, COAPT patients had a higher mean LVEF (MITRA-FR: 33% vs COAPT: 40%; p=0.077). Both groups remained similar with respect to ratio of moderate:severe MR (60:40% vs 64:36%), EROA (0.40+/-0.13 vs 0.38+/-0.15cm2), VC (0.6+/-0.2cm vs 0.6+/-0.2cm), LAVi (56+/-20ml/m2 vs 50+/-19ml/m2), LVEDVi (69+/-25ml/m2 vs 67+/-19ml/m2) and mortality (MITRA-FR: 40% vs COAPT: 35%). Conclusion: Post-acute MI, more patients with IMR met COAPT criteria (4.7%) than MITRA-FR echocardiographic criteria (1.7%) however both cohorts had similarly high mortality. Notwithstanding the difference in LVEF, MITRA-FR and COAPT echo criteria identified almost identical cohorts post-MI. Conflict of Interest: None